Importância da transmissão de conhecimento tácito no artesanato: inserido no produto de moda - Arraez, Solange Satomi Yanagu (2012)
The knowledge, the transmission of that knowledge, art and crafts, is part of human life since ancient times. Upon discovering the hands, the man discovered his creative potential, their ability to think and stop these knowledge and skills to develop bjects that will facilitate survival. Always complex issues and generate many different definitions, concepts and opinions. The aim of this study is to understand the importance of transmission of tacit knowledge in the craft and how to clarify through social interaction, what is held only in the mind of the holders of knowledge involving the world of crafts. Although for many years been considered handcraft rustic items, currently it has gained status as a luxury product, achieving high market prices. The partnership between fashion design and craftsmanship is yielding great creations that offer differential, originality, exclusivity and aesthetics. In this context, this study sought to explore the potential of those involved (learner - designer), for the purpose of perpetuating the techniques exposed the crafts and turn them into creative and productive experience in the development of fashion products.